Šūzubu, a Citizen of Uruk in the Sixth Century B.C. - Dandamayev, Muhammad A. (Anabasis. Studia Classica et Orientalia, 2010)
This paper is concerned with the activities of an official of the Eanna temple in the city of Uruk in Babylonia during the period 554–531 B.C. His name was Šūzubu and he was an overseer of the regular offerings in sheep to the Lady-of-Uruk (i.e. Ištar) and other deities. He also performed various other functions typical of the members of the temple personnel.